2020
DOI: 10.1101/2020.09.03.280842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Migration without interbreeding: evolutionary history of a highly selfing Mediterranean grass inferred from whole genomes

Abstract: Whole genome sequences and coalescence theory allow the study of plant evolution in unprecedented detail. In this study we extend the genomic resources for the wild Mediterranean grass Brachypodium distachyon to investigate the scale of population structure and its underlying history at whole-genome resolution. The analysis of 196 accessions, spanning the Mediterranean from Iberia to Iraq, shows that the interplay of high selfing and seed dispersal rates has shaped genetic structure. At the continental scale, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 106 publications
(148 reference statements)
0
10
0
Order By: Relevance
“…Other researchers working on inbred lines have reached similar conclusions, and used various methods to eliminate them e . g. Zea (Chia et al 2012; Lu et al 2015; Bukowski et al 2018) and Brachypodium (Stritt et al 2021). In human genetics, SNP-calling relies heavily on family trios, but in outcrossing organisms where this is not possible, there is great cause for concern.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers working on inbred lines have reached similar conclusions, and used various methods to eliminate them e . g. Zea (Chia et al 2012; Lu et al 2015; Bukowski et al 2018) and Brachypodium (Stritt et al 2021). In human genetics, SNP-calling relies heavily on family trios, but in outcrossing organisms where this is not possible, there is great cause for concern.…”
Section: Discussionmentioning
confidence: 99%
“…After years of collaborative work, the genotypic tools are available to do this with a large diversity panel of genotypes spanning from Spain to Iraq (Figure I) [27,, enabling better comprehension of population structure in B. distachyon and its drivers. As of today, five genetic clades whose divergence backdates to the upper Pleistocene have been described (Figure I) [37]. By exploiting niche modelling, genome-wide association studies, and genome-wide scans of selection analyses, recent works have defined how selection shaped genetic diversity at multiple temporal and spatial scales [31,[143][144][145] and identified genes under selection and involved in climate adaptation [143][144][145].…”
Section: Brachypodium: a Model To Study Biodiversity And Speciation I...mentioning
confidence: 99%
“…This ever-growing diversity panel will undoubtedly allow further dissection of how gene-environment interactions shape fitness-related traits in B. distachyon and, therefore, more widely in grasslands. For instance, there is still an active debate on whether the difference in flowering times is an important driver of B. distachyon population structure and the relative contribution of stressors such as drought tolerance [37,38,78,146]. In this context, exploring diversity of flowering genes [147][148][149][150][151] in the diversity panel will allow testing of whether flowering time evolved through neutral processes or selection.…”
Section: Brachypodium: a Model To Study Biodiversity And Speciation I...mentioning
confidence: 99%
“…The populations studied here were characterized by low levels of genetic diversity (mean He: 0.04; mean Ho: 0.02; mean π: 0.05), strongly positive inbreeding coefficient estimates (FIS), and a high degree of linkage disequilibrium (r¯d and IA) (Table 1), all of which are consistent with a mating system dominated by self-fertilization. While studies directly assessing the mating system of A. thurberianum are lacking, many closely related species from the Poaceae family have been described as self-fertilized (Jones and Nielson, 1989;Arnesen et al, 2017;Marques et al, 2017;Stritt et at. 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of effective migration (EEMS and unPC) also appeared strongly reduced among a number of geographically proximate populations (PT and DH separated by 58 km, or EW and FR separated by 127 km, for example, Figures 3b, c). While gene flow among spatially proximate populations can be high in some wind-dispersed grasses (Vogel et al, 2009; Stritt et al, 2022), pronounced spatial genetic structure has also been reported in Eurasian species of Stipeae (Wagner et al, 2011; Durka et al, 2013). Patterns of population differentiation and identifiability across both large and small geographic scales indicates that genetic variation in A. thurberianum has been shaped by a combination of historical isolation, local adaptation to environment, as well as life history variation.…”
Section: Discussionmentioning
confidence: 99%